Diffuse large B-cell lymphoma of the kidney: A rare neoplasm - Ram Narayan Das; Shatavisha Dasgupta; Soumya Mondal; Debraj Saha; Uttara Chatterjee (Wolters Kluwer Medknow Publications, 2013)
Primary renal lymphoma is a rare neoplasm, but it should be kept in mind in the differential diagnosis of renal neoplasms. A middle aged man presented with symptoms of weight loss, anorexia and fullness of the abdomen after meals. On clinical and radiological examination, a renal mass was revealed and operated upon. A diagnosis of primary high grade renal lymphoma was made on histopathological examination and immunohistochemically it was further classified as diffuse large B-cell lymphoma. Unfortunately, the patient died after 5 months of diagnosis in spite of three cycles of chemotherapy following surgery. The pathological details of rare tumor are presented here.